Coupling of the ecosystems in North China with the East Asian summer monsoon rainfall during the Holocene. (15th January 2023) - Zhao, Jiaju; Liu, Jianbao; Liu, Jinzhao; Chen, Shengqian; Wang, Li; Zhou, Aifeng; Zhang, Zhiping; Shen, Zhongwei; Chen, Jie; Chen, Lin; Cao, Yunning; Hu, Jing; et al.
Abstract: The influence of Holocene East Asian Summer Monsoon (EASM) rainfall on ecosystems over northern China remains controversial: delay or synchronization. Here we present Holocene quantitatively reconstructed temperature and salinity records based on alkenone proxies in the Dali Lake from northern China. Our data indicate that the Dali Lake was significantly diluted to a freshwater lake (0.8 ± 0.4 g/L) during ∼11.4–3.8 cal ka BP, relative to the modern brackish state. From the early Holocene (before 8.0 cal ka BP) to the middle Holocene (8.0–5.0 cal ka BP), the average salinity value of Dali Lake decreased by ∼0.3 g/L (ca. 30%), but our reconstructed temperature record shows an increase of ∼2.1 °C. In the context of climate warming, the evaporation was enhanced, and thus the decline in salinity is attributed to the increased precipitation, indicating a mid-Holocene EASM rainfall maximum. After comparing our reconstruction with vegetation data, we proposed that the stable and abundant EASM rainfall promoted the forest expansion and vegetation recovery over northern China during the mid-Holocene, suggesting the coupling of ecosystems and EASM rainfall in North China. Highlights: Group I Isochrysidales identified in Dali Lake during the early and middle Holocene. Dali Lake was a freshwater lake during the early and middle Holocene. Quantitative salinity and temperature reconstructions based on alkenone proxies. A 3000-yr delay between temperature and moisture optimum and local summer insolation maximum. Lake and terrestrial ecosystems and Holocene EASM rainfall were coupled in North China.